An experimental study on penetration and mixing characteristics of liquid fuel in preheated supersonic airflows. (January 2023) - Hwang, Byeong-Jo; Choi, Hojin; Min, Seongki
Abstract: The effect of air temperature on the penetration and mixing of a liquid hydrocarbon fuel injected into supersonic airflows was investigated. The supersonic air of Mach 1.8 with a total temperature in the range of 373–673 K was supplied to the test section. The liquid fuel was injected into the supersonic airflow by means of an alternating-wedge pylon with a fuel-to-air momentum flux ratio of 15. A laser sheet imaging system using Mie scattering has been used to investigate the instantaneous and ensemble-averaged characteristics of the fuel plume, the fuel/air mixing process, and fuel evaporation. As the air temperature increased, the Mie scattering signal gradually weakened due to fuel-air mixing enhancement and fuel evaporation downstream of the pylon. At an air temperature of 673 K, most of the fuel evaporated before reaching the outlet of the test section (X/d = 703). As the air temperature increased from 373 to 673 K, the total pressure loss without fuel injection decreased from 20.6 to 15.4%. In addition, the total pressure losses due to fuel injection was about 3.5% greater than that without fuel injection. As the air temperature increased, the fuel penetration height decreased. However, at the air temperatures higher than the fuel boiling temperature, the fuel jet/spray penetration heights were almost similar, showing little effect of temperature any further. Graphical abstract: Image 1 Highlights: The effect of air temperature on the penetration and mixing of a liquid fuel in supersonic airflows was investigated. The Mie scattering technique was used to visualize the mixing structure of liquid fuel in supersonic airflows. The effect of air temperature increase on the total pressure loss due to the pylon and fuel injection was investigated.